Developing a Transformation Agenda for Zimbabwe - Eppel, Shari (Book collections on Project MUSE., 2009)
Developing a Transformation Agenda for Zimbabwe analyses the political and economic constraints on the nation's reconstruction and democratic transformation and suggests options for transformation in key sectors as well as lessons learnt from other transformations. The challenges in relation to transitional justice are analysed from an historical context as well as in light of the political dynamics in the country. The urgent need to launch a stabilisation programme is discussed, along with key issues for economic reconstruction. The book also looks at military involvement in politics in Zimba.